2022
DOI: 10.1002/ecs2.4295
|View full text |Cite
|
Sign up to set email alerts
|

Migration in drought: Receding streams contract the seaward migration window of endangered salmon

Abstract: Prolonged migration windows buffer migratory animal populations against uncertainty in resource availability. Understanding how intensifying droughts from climate change influence the migration window is critical for biodiversity conservation in a warming world. We explored how drought affects the seaward migration of endangered coho salmon (Oncorhynchus kisutch) near the southern extent of their range in California, USA. We tracked stream departures of juvenile coho, measuring streamflow and temperature in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…It was surprising that the relationship was not stronger since multiple studies have suggested lower juvenile survival during lower outflow periods because of increased migration time and increased temperatures (Hance et al 2022). Similar results have been seen in other systems where droughts greatly decrease salmonid migration windows, survival probabilities, and habitat availability (Deitch et al 2018;Kastl et al 2022).…”
Section: Fishsupporting
confidence: 85%
“…It was surprising that the relationship was not stronger since multiple studies have suggested lower juvenile survival during lower outflow periods because of increased migration time and increased temperatures (Hance et al 2022). Similar results have been seen in other systems where droughts greatly decrease salmonid migration windows, survival probabilities, and habitat availability (Deitch et al 2018;Kastl et al 2022).…”
Section: Fishsupporting
confidence: 85%
“…Freshwater ecosystems are sensitive to anthropogenic flow regime alteration, which may cause temperature fluctuations. Close to its southernmost distribution, warming with low flows threaten coho salmon in California, and environmental flow protection is needed to support Pacific salmon in a changing climate [125]. Rapid temperature shifts have a negative impact on the hypo-osmoregulatory capacities of Atlantic salmon smolts [126].…”
Section: Smoltingmentioning
confidence: 99%
“…Accordingly, the long time series analysis of the timing of the smolt migration of Atlantic salmon in the River Bush, Northern Ireland, revealed that earlier downstream migration periods were evident across the time series [147]. Kastl et al [125] found that an increase from 10.2 to 12.8 • C in mean seasonal water temperature accelerated the migration window by three weeks in coho salmon living near its southern distribution range in California, USA.…”
Section: Smolt Migrationsmentioning
confidence: 99%